Effect of Asthma Gymnastic on Blood Nitric Oxide, Mood, Energy Expenditure and Sex Quality - Ita Juliastuti; Suradi Suradi; Debree Septiawan (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2021)
Background: Sex is a basic function in human life. Exercise stimulates formation of blood nitric oxide (NO) as a potent vasodilator in all organs of the body including the genitals. Exercise prevents and improves depression and anxiety, but the link between exercise and sexual function has received less attention. Asthma gymnastic is an exercise in pulmonary rehabilitation that everyone can practice it. The effect of asthma gymnastic in sexology has never been studied yet. Methods: The pretest and posttest experimental clinical trials were carried out on 40 people aged 40-60 years old in Surakarta on 21st July 2019 until 27th October 2019. The intervention group (n=20) were treated with asthma gymnastics once a week for 12 weeks while the control group (n=20) didn’t exercise regularly. The aims of this study are to assess the effect of asthma gymnastic on blood nitric oxide, mood based on the Beck Depression Inventory (BDI) questionnaire, energy expenditure (physical and sexual activity) and sex quality based on the Arizona Sexual Experiences Scale (ASEX) questionnaire. Results: Asthma gymnastic had a significant positive effect on blood NO (B=0.426;P<0.003), physical activity (B=0.664;P<0.001) and sexual activity (B=0.336;P=0.026). Asthma gymnastic had a significant negative effect on the BDI score (B=-0.664;P<0.001). Asthma gymnastic did not have a direct effect on sex quality (B=-0.071;P=0.756). BDI score had a positive effect on sex quality (B=0.464;P=0.009). NO blood levels had no effect on sex quality (B=0.018;P=0.904). Conclusion: Asthma gymnastic had no direct effect on sex quality, but it increased blood NO, energy expenditure and improved mood. Asthma gymnastic would have significant effect on improving sex quality if supported by good mood.